Economic Empowerment Impact in Indonesian Pesantren: Advice for Government and Future Research - M Bastomi Fahri Zusak (Pustaka Peradaban, 2024)
This paper develops a scoping study approach to review the literature on Pesantren (Islamic Boarding Schools) and their role in economic development. Over the past 15 years, published papers have been categorized into several key topics, including entrepreneurship, leadership, empowerment, multiculturalism, and politics. Among these, leadership has emerged as the most researched topic, given the kyai's role as influential religious, social, and cultural figures. Multiculturalism and politics are also prominently featured in the literature. This study highlights the importance of economic empowerment within pesantren and offers policy recommendations for the government while suggesting future research directions to strengthen pesantren's contributions to Indonesia's socio-economic landscape.